Abundance of Zooplankton in Ramsagar-Dighi, Dinajpur, Bangladesh (Bangladesh Journal of Zoology, 2016)
The present study was carried out from May, 2011 to March, 2012 which deals with the abundance of zooplankton in Ramsagardighi, Dinajpur, Bangladesh. A total of 27 species of 21 genera were recorded in which rotifers were more abundant with 9 genera and 12species followed by copepods with 6 genera and 7 species and cladocerans with 5 genera and 7 species from the study area. A crustacean, nauplius larva was also recorded from the study area. Monthly fluctuation of some physico-chemical parameters was also noted.Bangladesh J. Zool. 43(2): 303-312, 2015